Anti-biofilm and anti-virulence potential of cell free supernatant of Akkermansia muciniphila against Salmonella - Jiaxiu Liu; Wenxiu Zhu; Huanhuan Liu; Xiaomeng Ren; Ningbo Qin; Xiaodong Xia (Food Science and Human Wellness)
Akkermansia muciniphila is one of the commensals residing within the mammalian gut and co-evolving with the host. Numerous studies have demonstrated the benefits of A. muciniphila in ameliorating metabolic disorders, while little is known about the antimicrobial potential of A. muciniphila against pathogens. Here, we examined the antimicrobial and anti-virulence properties of cell free supernatant (CFS) of A. muciniphila against Salmonella Typhimurium. CFS retarded bacterial growth and inhibited the motility of S. Typhimurium SL1344 and S. Typhimurium 14028. CFS dose-dependently reduced cell hydrophobicity and auto-aggregation of both strains. Also, CFS from A. muciniphila significantly attenuated biofilm formation. Compared with untreated bacteria, CFS-treated bacteria significantly decreased adhesion and invasion to Caco-2 cells, and reduced intracellular survival in macrophages. CFS maintained antimicrobial properties after treatment with high temperatures and various proteases, while it lost its antimicrobial activity after pH neutralization. Gas chromatography-mass spectrometry (GC-MS) confirmed that A. muciniphila produced a certain amount of acetate and propionate, and ultra-high-performance liquid chromatography-mass spectrometry (UHPLC-MS) identified other organic acids and metabolites in CFS. In summary, CFS from A. muciniphila exhibited anti-biofilm and anti-virulence properties against Salmonella and could be potentially utilized in the food industry for controlling Salmonella contamination and reducing infection.